Fluorescent‐ and tagged‐protoxin II peptides: potent markers of the Nav1.7 channel pain target. (14th May 2021) - Montnach, Jérôme; De Waard, Stephan; Nicolas, Sébastien; Burel, Sophie; Osorio, Nancy; Zoukimian, Claude; Mantegazza, Massimo; Boukaiba, Rachid; Béroud, Rémy; Partiseti, Michel; Delmas, Patrick; Marionneau, Céline; et al.
Abstract : Background and Purpose: Protoxin II (ProTx II) is a high affinity gating modifier that is thought to selectively block the Nav 1.7 voltage‐dependent Na + channel, a major therapeutic target for the control of pain. We aimed at producing ProTx II analogues entitled with novel functionalities for cell distribution studies and biochemical characterization of its Nav channel targets. Experimental Approach: We took advantage of the high affinity properties of the peptide, combined to its slow off rate, to design a number of new tagged analogues useful for imaging and biochemistry purposes. We used high‐throughput automated patch‐clamp to identify the analogues best matching the native properties of ProTx II and validated them on various Nav ‐expressing cells in pull‐down and cell distribution studies. Key Results: Two of the produced ProTx II analogues, Biot‐ProTx II and ATTO488‐ProTx II, best emulate the pharmacological properties of unlabelled ProTx II, whereas other analogues remain high affinity blockers of Nav 1.7. The biotinylated version of ProTx II efficiently works for the pull‐down of several Nav isoforms tested in a concentration‐dependent manner, whereas the fluorescent ATTO488‐ProTx II specifically labels the Nav 1.7 channel over other Nav isoforms tested in various experimental conditions. Conclusions and Implications: The properties of these ProTx II analogues as tools for Nav channel purification and cell distribution studies pave the way for a better understanding of ProTx II channel receptors in pain and their pathophysiological implications in sensory neuronal processing. The new fluorescent ProTx II should also be useful in the design of new drug screening strategies.